The use of frozen plasma samples in thromboelastometry - Schoergenhofer, Christian (Clin Exp Med, 2017)
Thromboelastometry is increasingly used in the clinical and scientific setting. The use of frozen plasma samples may be useful in overcoming certain limitations such as local and timely availability. Whole blood (WB) samples of 20 healthy volunteers were obtained, and plasma was generated. NATEM (n = 20), EXTEM (n = 20) and INTEM (n = 8) analyses were performed in WB, fresh plasma and frozen and thawed plasma. Dabigatran (500, 1000 ng/ml), rivaroxaban (100, 200 ng/ml) or alteplase (333 ng/ml) were added ex vivo to WB, and thromboelastometry was performed in WB and in frozen and thawed plasma samples. Clot formation time, mean clot firmness and the area under the curve were significantly altered in plasma compared to WB. In INTEM and EXTEM analysis, clotting time (CT) was comparable between WB (100%) and fresh (INTEM 114% and EXTEM 93%, ratio of the means) and frozen plasma samples (85 and 99%), whereas in NATEM analysis, the CT increased in fresh (193%) and frozen plasma samples (130%). Dabigatran dose-dependently increased the CT approximately 5- and 9-fold in WB and even more pronounced 10- and 26-fold in plasma. Accordingly, rivaroxaban dose-dependently increased the CT 2- and 2.7-fold in WB, and 3.5- and 4-fold in plasma samples. Hyperfibrinolysis was achieved by addition of alteplase in all WB samples and was reproducible in plasma samples. In conclusion, thromboelastometry, especially INTEM and EXTEM analyses, is possible using frozen and stored plasma samples with comparable results to the corresponding whole blood samples.